The specialist - Stallone, Sylvester; Stone, Sharon, 1958-; Weintraub, Jerry; Llosa, Luis; Warner Bros; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 1998)
Hired by May Munro to bomb the mobsters who murdered her parents, ex-CIA explosives expert Ray Quick faces an ominous question: is May falling for him, or is she setting him up, too?
Title from container
Co-producer, R.J. Louis ; executive producers, Steve Barron, Jeff Most, Chuck Binder ; writer, Alexandra Seros ; music, John Barry
Performers: Sylvester Stallone, Sharon Stone, James Woods, Rod Steiger, Eric Roberts
Keywords: Gangster films; Action and adventure films; Feature films